Up-to-date monitoring data of wastewater and stormwater quality in Germany. (1st September 2021) - Nickel, Jan Philip; Sacher, Frank; Fuchs, Stephan
Highlights: New data on pollutant concentrations in german urban wastewater systems available. Treatment plants, combined sewer overflows, and stormwater outfalls considered. Harmonised sampling approach with up to 95 different substances analyzed. Data qualified to be used as representative input data for emission estimation. Abstract: A comprehensive dataset of pollutant concentrations in German urban wastewater systems is available from recently completed monitoring projects. It contains up to 1000 concentration values for each of 79 substances in wastewater treatment plant (WWTP) effluents from 49 sites, and up to 157 values for each of 95 substances in combined sewer overflows (CSOs) from 12 sites. WWTP influents and stormwater outfalls were sampled to a lesser extent. All sampling methods were harmonised and aimed at collecting event or multi-day composite samples over periods of ≥1 year. Among the substances analysed were biocides and pesticides, polycyclic aromatic hydrocarbons, perfluorinated alkyl substances, metals, pharmaceuticals, benzotriazoles, phenols, acesulfame, di-(2-ethylhexyl)phthalate, and hexabromocyclododecanes. Occurrence, concentration ranges, and removal rates of selected WWTPs are presented. CSOs can be confirmed as an important pathway of metals and PAH to receiving waters when compared to WWTPs on the basis of annual per capita loads. The derived volume-weighted site mean concentrations are qualified to be used as representative input data for estimation of average substance emissions in large areas, e.g. on river basin scale, if no site-specific data are available. As such, they will contribute to the development of strategies to reduce substance emissions, taking into account not only WWTPs but also stormwater-related discharges. Graphical abstract: Image, graphical abstract